Stowaways in the catch: Identification of Xenobrama microlepis in the haul fishery for Brama australis - Canales-Aguirre, Cristian B.; Herrera-Yáñez, Victoria; Ferrada-Fuentes, Sandra; Galleguillos, Ricardo (Revista de Biología Marina y Oceanografía, 2018)
Species that occur in low abundances and that are morphologically similar to the target fish are often undetectable in fisheries hauls; however, they add to the catch statistics of the target species. Using mitochondrial DNA and phylogenetic approaches we identified 6 individuals of the species Xenobrama microlepis in a haul targeting the southern Ray’s bream (Brama australis) taken by artisanal fishermen close to Chilean coast. The presence of X. microlepis increases the regional marine biodiversity of fishes in Chilean waters, and fisheries managers should pay attention to the hidden biodiversity in the fishery statistics.